Representation of Auditory Task Components and of Their Relationships in Primate Auditory Cortex - Knyazeva, Stanislava; Selezneva, Elena; Gorkin, Alexander; Ohl, Frank W.; Brosch, Michael (Frontiers in Neuroscience, 2020)
The current study aimed to resolve some of the inconsistencies in the literature on which mental processes affect auditory cortical activity. To this end, we studied auditory cortical firing in four monkeys with different experience while they were involved in six conditions with different arrangements of the task components sound, motor action, and water reward. Firing rates changed most strongly when a sound-only condition was compared to a condition in which sound was paired with water. Additional smaller changes occurred in more complex conditions in which the monkeys received water for motor actions before or after sounds. Our findings suggest that auditory cortex is most strongly modulated by the subjects' level of arousal, thus by a psychological concept related to motor activity triggered by reinforcers and to readiness for operant behavior. Our findings also suggest that auditory cortex is involved in associative and emotional functions, but not in agency and cognitive effort.